A morphometric study of the human fetal heart on post‐mortem 3‐tesla magnetic resonance imaging. (4th March 2013) - Sandaite, Inga; De Catte, Luc; Moerman, Philippe; Gewillig, Marc; Fedele, Luigi; Deprest, Jan; Claus, Filip
ABSTRACT: Objective: To report on the feasibility of assessing cardiac structures on post‐mortem 3‐tesla MRI (pmMRI) and to provide morphometric data in fetuses without cardiac abnormalities. Methods: Retrospective single center study on 3T pmMRI of 39 consecutive fetuses without cardiac abnormalities (13–38 weeks of gestation). Fetal cardiac anatomy was assessed and measurements of cardiac structures were performed on T2‐weighted 3D multiplanar reconstructed images. Linear regression analysis was performed to examine changes of cardiac dimensions during gestation. Results: The four‐chamber view of the fetal heart could be obtained and the measurements of cardiac chambers and ventricular walls could be performed in all 39 cases. The aorta and the pulmonary artery were visualized and their diameters were measured in 38 (97.4%) fetuses, ductus arteriosus in 32 (82%). All measurements showed strong linear correlation with gestational age. The relationship of the diameters of the pulmonary artery, aorta, and ductus arteriosus remained constant over pregnancy. All these observations are consistent with what is known from prenatal ultrasound. Conclusions: The present study proves the feasibility of visualizing normal cardiac structures on 3‐tesla pmMRI in fetuses beyond 14 weeks. We provide morphometric data that may enable diagnostic evaluation of cardiac abnormalities on pmMRI. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Post‐mortem fetal magnetic resonance imaging (pmMRI) is a valuable addition or alternative for conventional autopsy examination. Studies investigating the normal fetal anatomy on pmMRI are sparse. What does this study add? This study (1) comprehensively describes the methodology of the assessment of the normal fetal heart on pmMRI and (2) provides morphometric data helpful for the diagnostic evaluation of cardiac abnormalities on pmMRI.